2021
DOI: 10.1016/j.jsat.2020.108159
|View full text |Cite
|
Sign up to set email alerts
|

Youth OUD treatment during and after COVID: Increasing family involvement across the services continuum

Abstract: Telehealth innovations in substance use treatment necessitated by the COVID-19 pandemic present a generational opportunity to increase family involvement in medication for opioid use disorders (MOUD) among youth. This commentary describes a conceptual framework for engaging and retaining youth and families across four stages of MOUD services: Preparation, Initiation, Stabilization, Remission & Recovery. Case vignettes illustrate provider-delivered and direct-to-family tele-interventions for augmenting family i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…One might argue, however, that telehealth, by its nature, is a home‐based therapy. When we enter clients’ homes, we enter into their family system and have greater access to multiple family members (Hogue et al, 2020). This offers both therapeutic and pragmatic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…One might argue, however, that telehealth, by its nature, is a home‐based therapy. When we enter clients’ homes, we enter into their family system and have greater access to multiple family members (Hogue et al, 2020). This offers both therapeutic and pragmatic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Youth, pregnant women and incarcerated people with OUD are taken into consideration by some authors, given that they are more vulnerable [ 25 ▪ , 45 47 ]. To ensure continuation of treatment for youth with OUD and to reduce COVID-19 associated risks, authors reported implementation of mobile van delivery of extended-release medications [ 25 ▪ ].…”
Section: Responses and Strategies To Maintain Opioid Treatment Programs During The Pandemicmentioning
confidence: 99%
“…To ensure continuation of treatment for youth with OUD and to reduce COVID-19 associated risks, authors reported implementation of mobile van delivery of extended-release medications [ 25 ▪ ]. Authors suggest that the COVID-19 pandemic also created a generational opportunity to augment family involvement in tele-intervention across the youth OUD services continuum [ 45 ]. For pregnant women, regulations that have an adverse influence can be changed and telepsychology services integrated with existing treatment programs [ 48 , 49 ].…”
Section: Responses and Strategies To Maintain Opioid Treatment Programs During The Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral services for youth with substance use problems can be conceptualized as a continuum—sometimes called a services cascade—consisting of the routine sequence of activities experienced by any given youth as they progress through the substance use services system ( Belenko et al, 2017 ; Knight et al, 2016 ). For heuristic purposes specific to OUD, Figure 1 depicts this continuum as a client flow chart anchored by four overlapping stages (see also Hogue et al, 2021 ). Note that youth who enter the OUD services system typically experience episodic increases and decreases in opioid use—that is, a chronic course-of-disorder marked by regular use, remission, and recurrence—over a given time span ( Buckheit et al, 2018 ; Fishman, Wenzel, Scodes, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%